2023
DOI: 10.29413/abs.2023-8.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid status and TNF-alpha in post-reproductive women with COVID-19 and 12 months after the disease

N. V. Semenova,
S. I. Kolesnikov,
E. V. Vyrupaeva
et al.

Abstract: The aim. To assess the thyroid status and its relationship with tumor necrosis factor alpha (TNF-alpha) in post-reproductive women in the acute phase of the COVID-19 of moderate course and 12 months after the disease.Materials and methods. 85 women aged 45 to 69 years were divided into groups: women without COVID-19, not vaccinated, with no antibodies to COVID-19 (IgG) – control group (n = 15); women in the acute phase of COVID-19 of a moderate course, accompanied by pneumonia – main group (n = 57); patients f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…During menopause, women begin to experience agerelated neuroendocrine changes, accompanied by estrogen deficiency, which is considered as a condition for higher vulnerability to moderate and severe COVID-19 and subsequent complications [1]. It has been shown that menopausal women even 1 year after COVID-19, experience physical and emotional health problems, which may be due to endothelial dysfunction [2,3]. One of the mechanisms for the development of endothelial dysfunction is oxidative stress that develops during SARS-CoV-2 virus infection [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…During menopause, women begin to experience agerelated neuroendocrine changes, accompanied by estrogen deficiency, which is considered as a condition for higher vulnerability to moderate and severe COVID-19 and subsequent complications [1]. It has been shown that menopausal women even 1 year after COVID-19, experience physical and emotional health problems, which may be due to endothelial dysfunction [2,3]. One of the mechanisms for the development of endothelial dysfunction is oxidative stress that develops during SARS-CoV-2 virus infection [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%